Changes in the inner ear structures in cystic fibrosis patients. (January 2017) - Pauna, Henrique F.; Monsanto, Rafael C.; Kurata, Natsuko; Paparella, Michael M.; Cureoglu, Sebahattin
Abstract: Objective: Although prolonged use of antibiotics is very common in cystic fibrosis (CF) patients, no studies have assessed the changes in both cochlear and peripheral vestibular systems in this population. Methods: We used human temporal bones to analyze the density of vestibular dark, transitional, and hair cells in specimens from CF patients who were exposed to several types of antibiotics, as compared with specimens from an age-matched control group with no history of ear disease or antibiotic use. Additionally, we analyzed the changes in the elements of the cochlea (hair cells, spiral ganglion neurons, and the area of the stria vascularis). Data was gathered using differential interference contrast microscopy and light microscopy. Results: In the CF group, 83% of patients were exposed to some ototoxic drugs, such as aminoglycosides. As compared with the control group, the density of both type I and type II vestibular hair cells was significantly lower in all structures analyzed; the number of dark cells was significantly lower in the lateral and posterior semicircular canals. We noted a trend toward a lower number of both inner and outer cochlear hair cells at all turns of the cochlea. The number of spiral ganglion neurons in Rosenthal's canal at the apical turn of the cochlea was significantly lower; furthermore, the area of the stria vascularis at the apical turn of the cochlea was significantly smaller. Conclusions: Deterioration of cochlear and vestibular structures in CF patients might be related to their exposure to ototoxic antibiotics. Well-designed case-control studies are necessary to rule out the effect of CF itself.